Applying Fuzzy Analytic Hierarchy Process (FAHP) -Cut Based and TOPSIS Methods to Determine Bali Provincial Road Handling Priority - Wedagama D.M.P.; Frederika A. (Civil Engineering Dimension, 2011)
The Analytic Hierarchy Process (AHP) method has been employed in a previous study to determine Bali provincial road handling priority. This method usually overlooks the decision maker’s degrees of confidence and optimism of the decision. Meanwhile, Fuzzy Analytic Hierarchy Process (FAHP) -cut based and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods allow the researcher to estimate the overall road handling priority considering on degrees of confidence and optimism of the decision. The present study aims at determining Bali provincial road handling priority using FAHP -cut based and TOPSIS methods. The current study shows that decision makers’ degree of confidence in both pessimistic and moderate situations and optimism from certain to the most uncertain conditions suggesting the same road link as the highest priority compared to the previous study. Both current and previous studies also conclude the same road link as the lowest road handling priority.